2012 IEEE Vehicular Technology Conference (VTC Fall) 2012
DOI: 10.1109/vtcfall.2012.6399305
|View full text |Cite
|
Sign up to set email alerts
|

Bit Error Rate Performance of Generalized Frequency Division Multiplexing

Abstract: Abstract-Generalized frequency division multiplexing is a non-orthogonal, digital multicarrier transmission scheme with attractive features that address the requirements of emerging applications of wireless communications systems in areas like cognitive radio and machine-to-machine communication. In this paper, first a linear system description is obtained for the transmitter by ordering data in a time-frequency block structure and representing the processing steps upconversion, pulse shaping and upsampling as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 3 publications
(4 reference statements)
2
73
0
4
Order By: Relevance
“…This is because the MMSE scheme produces no inherent noise enhancement. It is important to note that similar observations were also highlighted within a recent study found in [19].…”
Section: Detection Performance With Mmse-based Gfdm Receiversupporting
confidence: 89%
See 1 more Smart Citation
“…This is because the MMSE scheme produces no inherent noise enhancement. It is important to note that similar observations were also highlighted within a recent study found in [19].…”
Section: Detection Performance With Mmse-based Gfdm Receiversupporting
confidence: 89%
“…(19), the magnitudes of Z u result in an impulse function in a similar manner to an auto-correlation function. Hence, the magnitude z u ½w (derived from Z u ) can be approximated to…”
Section: Tdc Decision Criterionmentioning
confidence: 96%
“…Three common linear receivers, i.e., zero-forcing (ZF), matched filter (MF), and minimum mean square error (MMSE) receivers, are evaluated for the receiver side of GFDM. Among GFDM linear receivers, GFDM MMSE receiver yields the lowest error rate at the cost of the highest complexity which makes it unusable for many applications [10]. Therefore, matched filter (MF) receiver in combination with the double-side successive interference cancellation (DSIC) algorithm is used instead to provide a trade-off between computational complexity and bit error rate (BER) performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…FBMC (Filter Bank Multicarrier) [1], UFMC (Universal Filtered Multicarrier) [2], GFDM (Generalized Frequency Multicarrier Multiplexing) [3,4] and so on are examples of these so called "New Waveforms". Since these schemes have less OOB (out-of-band) emissions in general, more efficient spectrum usage is expected.…”
Section: Introductionmentioning
confidence: 99%
“…However in this paper, in order to reduce the interference to OFDM signal and to match the definition in generating OFDM signal, Eq. (3) is used as defined in [4].…”
Section: Introductionmentioning
confidence: 99%